The Influence Of Customer Reviews, Customer Trust, And Customer Experience On Facetology Sunscreen Customer Loyalty In Generation Z - Pebriyanti, Dwi; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2025)
Research aim : Examination determine effect customer review, customer trust, and customer experience on sunscreen facetology customer loyalty in generation Z. Design/Methode/Approach : Using a quantitative approach and type of causality analysis. The total sample used was 100 respondents with purposive sampling technique. Data analysis was carried out by classical assumption test, multiple linear regression test, coefficient of determination, and hypothesis testing using IBM SPSS Statistics 22 program. Research Finding : Partially customer review variable, customer trust doess not signnificant effecct on customer loyallty, while custommer experience variable effeect on customer loyallty. Customer review, customer trust, and customer experience simultaneously affect facetology sunscreen customer loyalty in generation Z. Theoretical contribution/Originality : Customer loyalty occurs when individuals are accustomed to purchasing products provided and often interacts and makes purchases within a certain period of time, while remaining loyal to all offers from the company. Practitionel/Policy implication : Examination facetology sunscreen products through shopee in maintaining and increasing customer loyalty. Research limitation : This research examines strategies for customer loyalty with a focus on customer reviews, customer trust, and customer experience for Facetology sunscreen products for generation Z in Nganjuk Regency through Shopee.